Pengaruh Health Consciousness dan Environmental Awareness Terhadap Purchase Intention Wedang Uwuh Instan Berkemasan Ramah Lingkungan di Kota Surakarta: Model TPB yang Diperluas - Prameswari, Dewani Anindita Mega; Isa, Muzakar (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF HEALTH CONSCIOUSNESS AND ENVIRONMENTAL AWARENESS ON THE PURCHASE INTENTION OF ENVIRONMENTALLY FRIENDLY PACKAGING INSTANT WEDANG UWUH IN THE CITY OF SURAKARTA: AN EXPANDED TPB MODELThis study aims to expand empirical insights into environmentally friendly purchasing behavior by examining the effects of health consciousness and environmental awareness on consumers’ purchase intention toward eco-packaged instant wedang uwuh. The research is grounded in the Theory of Planned Behavior (TPB), which positions attitude, subjective norm, and perceived behavioral control as central constructs influencing behavioral intention. A quantitative causal design was applied, and primary data were collected through a Google Form questionnaire completed by 302 respondents in Surakarta City. SmartPLS was employed to analyze direct effects as well as mediation pathways, providing a comprehensive understanding of intervariable relationships. The findings indicate that several hypotheses were not supported, including the effect of attitude on purchase intention, the direct effect of environmental awareness on purchase intention, and the influence of health consciousness on subjective norm. Nevertheless, health consciousness significantly affected attitude, perceived behavioral control, and purchase intention. Moreover, environmental awareness showed significant effects on attitude, subjective norm, and perceived behavioral control, highlighting its importance in shaping consumer evaluations and perceived behavioral capabilities. Mediation analysis revealed two significant indirect pathways: mediation through subjective norm and perceived behavioral control in the relationship between environmental awareness and purchase intention. Meanwhile, other mediation pathways demonstrated positive directions but did not reach statistical significance.